All‐Solution‐Processed Red and Orange‐Red Organic Light‐Emitting Diodes with High‐Efficiencies: The Effect of Mixed‐Host Emissive Layers and Thermal Annealing Treatment. Issue 9 (4th June 2019) - Chang, Yu‐Fan; Yang, Lan‐Sheng; Su, Hsiao‐Tso; Liao, Si‐Yi; Niu, Mu‐Chun; Mahesh, K. P. O.; Chen, Chao‐Hsuan; Chao, Yu‐Chiang; Meng, Hsin‐Fei; Huang, Heh‐Lung; Chao, Teng‐Chih; Tseng, Meu‐Rurng; et al.
Abstract: The instability of the organic light‐emitting diodes (OLEDs) during operation can be attributed to the existence of point defects on the organic layers. In this work, the effect of mixed‐host emissive layer and the thermal annealing treatment were investigated to eliminate defects and to boost the device performance. The mixed‐host system includes 4, 4′, 4′′‐tri (9‐carbazoyl) triphenylamine (TCTA) and 2, 7‐bis(diphenylphosphoryl)‐9, 9′‐spirobi[fluorene] (SPPO13). The mixed‐host emissive layer with thermal annealing treatment showed low roughness and few pinholes, and the devices fabricated from this emissive layer exhibited high efficiencies, high stabilities, and long lifetimes. The red and orange‐red OLEDs exhibited efficiencies of 13.9 cd/A and 24.35 cd/A, respectively. The longest half‐lifetime (L0 =500 cd/m 2 ) of the red and orange‐red OLEDs were 158 h and 180 h, respectively. Efforts were made to solve problems in large‐area coating and to reduce the number of defects on in organic layer. Large‐active‐area (active area=3 cm×4 cm) red phosphorescent OLEDs (PhOLEDs) devices were realized with very high current efficiency up to 9 cd/A. Abstract : The influences of mixed‐host emissive layers comprising 4, 4′, 4′′‐tri (9‐carbazoyl) triphenylamine (TCTA) and 2, 7‐bis(diphenylphosphoryl)‐9, 9′‐spirobi[fluorene] as well as thermal annealing treatment on the performance of red and orange large‐area light‐emitting diodes were investigated. Defects in the organic layers could be minimized by tuning the fabrication conditions.